Highly twisted ladder-type backbone bearing perylene diimides for non-fullerene acceptors in organic solar cells. (February 2019) - Cheng, Jiarun; Li, Bing; Ren, Xiaojie; Liu, Feng; Zhao, Hongchi; Wang, Haijun; Wu, Yonggang; Chen, Weiping; Ba, Xinwu
Abstract: A ladder-type π-system PDIPY that bearing perylene diimide and pyrene units have been developed for constructing non-fullerene acceptors. The vinyl bridged PDIPY dimerPDIPY-V and polymerPPDIPY-V have been synthesized via bromonation and Stille coupling recation.PDIPY-V andPPDIPY-V exhibit intense and broad absorption within 400–650 nm that complement the absorption spectra of the narrow bandgap polymeric donors. DFT calculation indicated thatPDIPY-V andPPDIPY-V hold highly twisted structure, which prevent the formation of π−π stacking and crystallization in the aggregated states. The grazing-incidence wide-angle X-ray scattering (GIWAXS) and atomic force microscopy (AFM) investigations confirmed the amorphous nature of the pure films and thePDIPY-V /PPDIPY-V :PTB7-Th blend films. ThePDIPY-V :PTB7-Th based photovoltaic device showed a poor performance due to the small LUMO offset of donor and acceptor. While thePPDIPY-V :PTB7-Th based device showed a high PCE of 5.20%, indicating thePDIPY derivatives are promising non-fullerene acceptors for polymer solar cells. Highlights: Ring-fused ladder-type non-fullerene acceptors were synthesized. The highly twisted structure prevent excessive aggregation of the acceptors. The acceptors covered a broad absorption region from 400 nm to 650 nm. The non-fullerene solar cells achieved a high PCE of 5.20%.